A gnawing question... - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Anna M Mutinda (Ministry of Agriculture and Rural Development, PO Box 4298, Kitale, Kenya), is pursuing her Masters degree in crop protection, focussing on vertebrate pests, especially rodents. She writes to ask fellow readers to send her 'current...